Event Schemata of Journalists Plays Integral Role in Describing Foreign Relations: A Glimpse of Entman’s Framing Perspective through Analysis of Media Framing Of Pak-Afghan Foreign Policy during 2015-2021 - Nawaz, Fehmida; Yousaf, Muhammad (Pakistan Languages and Humanities Review, 2023)
The present study was conducted to find out the press framing of foreign policies and relations between Pakistan and Afghanistan. These relations are described under conceptual model of ‘Cascading Model of Framing’ presented by veteran media framing scholar Entman (2009). The proposition he suggested for measuring the variables used in current study as hypothesis. Two main concepts in framing introduced by Entman: source of information and ‘event schemata’. This longitudinal study was consisted of four newspapers’ editorial analysis The Nation, Daily Dawn, Afghanistan Times and Daily Outlook Afghanistan from 2015 to 2021. Sample was selected through purposive sampling. Content analysis was method of data analysis. Data, using cross tab test data was analyzed. The main findings of this study were as: govt. of both countries was major source of framing and after 2015, media routines were at highest in describing events proving event schemata as key in interpretive issues and events.